1979
DOI: 10.1007/bf02441240
|View full text |Cite
|
Sign up to set email alerts
|

EDTA soluble protein of human mature normal enamel

Abstract: Pure human mature enamel was prepared using a careful microdissection technique. After EDTA dissolution, the soluble proteins were recovered representing a concentration of 0.035% in the initial enamel. When the samples were analyzed with polyacrylamide gel electrophoresis, Coomassie Brilliant Blue staining revealed only one sharp fast migrating band, whereas o-toluidine blue, methylene blue, Amido Black 10B, and pyronine red G showed a thin double band at the same migration distance. Ultracentrifugation studi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
13
0

Year Published

1980
1980
2016
2016

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 24 publications
(13 citation statements)
references
References 20 publications
0
13
0
Order By: Relevance
“…A high molecular weight (160,000-200,000 daltons) Stains-All-positive protein band was observed in all hamster enamelin fractions on SDS gels. The amino acid composition of this partially purified hamster enamel crystal protein was comparable to that of adult bovine and human enamel matrix proteins [30,32].…”
Section: Discussionmentioning
confidence: 84%
“…A high molecular weight (160,000-200,000 daltons) Stains-All-positive protein band was observed in all hamster enamelin fractions on SDS gels. The amino acid composition of this partially purified hamster enamel crystal protein was comparable to that of adult bovine and human enamel matrix proteins [30,32].…”
Section: Discussionmentioning
confidence: 84%
“…In the present study, the acid was not admixed with the proteolytic enzyme pepsin, as it had been in a previous study . The amount of organic matrix in enamel is very low (0.035%) [Belcourt and Gillmeth, 1979] and even for dentine, no influence of pepsin admixture on the erosive/abrasive tooth wear could be observed. Toothbrushing was performed before erosion and 1 h after the last erosive attack per day to follow the recommendations made for patients suffering from erosion [Lazarchik and Filler, 1997;Wiegand et al, 2008], although there are studies showing that the period between erosion and toothbrushing has only a minor effect on the erosion/ abrasion tooth wear .…”
Section: Discussionmentioning
confidence: 99%
“…This suggests that all the protein present in mature enamel is tightly bound to apatite crystals, a characteristic typical of the enamelin class of enamel proteins [Termine et al, 1980]. The guanidine-EDTA soluble fraction contained a glycoprotein of low molecular weight (~ 2,000-3,000) having an amino acid composition including the presence of hydroxyproline almost identical to that described previously using an isola tion procedure employing only EDTA [Belcourt and Gillmeth, 1979], The guanidine-EDTA insoluble residue contained lactic acid-soluble glycoprotein similar in size and amino acid composition to that which became solubilized in EDTA under the same extraction conditions. The amino acid compositions of both the HET-E and the LAC protein fractions are similar to the data of Robinson et al [1975] for mature human enamel 'tuft' protein prepa rations, although the analyses of this study (table I) showed markedly higher propor tions of glycine and serine, and higher pro portions of hydroxyproline.…”
Section: Discussionmentioning
confidence: 67%
“…Concomitant with this change, the amino acid composi tion of the enamel organic matrix undergoes substantial modification from an early ma trix containing high percentages of glutamic acid, proline, leucine and histidine to a fully mineralized matrix having substantially in creased proportions of aspartic acid, serine and glycine [Eastoe, 1960[Eastoe, , 1963Glimcher et al, 1961;Fincham, 1971Fincham, , 1980Eggert et al, 1973;Robinson et al, 1977], In a previous study [Belcourt and Gillmeth, 1979] it was found that an acidic gly-coprotein of low molecular weight was solu bilized after extraction of pure normal ma ture human enamel in 0.4 M EDTA, pH 7.2. However, an insoluble residue always remained, even after extensive EDTA ex traction.…”
mentioning
confidence: 99%